Partner support and prenatal anxiety: A systematic review integrating biopsychosocial and dyadic mechanisms - Nurul Jannah; Sri Lestari; Lisnawati Ruhaena (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Pregnancy is a critical period characterized by substantial physiological and psychosocial changes that increase vulnerability to stress and prenatal anxiety. Partner support has been identified as a key protective factor; however, existing studies often conceptualize social support broadly, with limited integration of relational and dyadic mechanisms. Purpose: To synthesize evidence on the relationship between partner support and prenatal anxiety within a biopsychosocial and dyadic framework. Method: Following PRISMA 2020 guidelines, systematic searches were conducted in PubMed, Scopus, and Google Scholar, identifying 10 eligible studies published between 2016 and 2025. The included studies were predominantly cross-sectional, with some longitudinal and dyadic designs. Data were extracted using a PICOS framework and synthesized through thematic analysis to identify patterns of association and underlying mechanisms. Results: Evidence across studies consistently indicates that higher levels of partner support are associated with lower prenatal anxiety, although findings are largely derived from observational designs. The relationship operates through both direct and indirect pathways. Relationship quality and dyadic coping emerge as key relational mechanisms that mediate or strengthen the association between support and maternal psychological outcomes. Additionally, dyadic evidence suggests that prenatal anxiety is shaped by interdependent processes within couples, highlighting the relational nature of maternal mental health. Conclusions: This review supports a biopsychosocial and dyadic understanding of prenatal anxiety and proposes a multi-pathway conceptual model integrating partner support, relationship quality, and dyadic coping. While the findings highlight the importance of partner involvement in antenatal care, further longitudinal and theory-driven studies are needed to establish causal pathways and strengthen the evidence base.